Neighborhood choices, neighborhood effects and housing vouchers - Morris A. Davis; Jesse Gregory; Daniel A. Hartley; Kegon T. K. Tan (Federal Reserve Bank of Chicago, 2017)
We study how households choose neighborhoods, how neighborhoods affect child ability, and how housing vouchers influence neighborhood choices and child outcomes. We use two new panel data sets with tract-level detail for Los Angeles county to estimate a dynamic model of optimal tract-level location choice for renting households and, separately, the impact of living in a given tract on child test scores (which we call "child ability" throughout). We simulate optimal location choices and changes in child ability of the poorest households in our sample under various housing-voucher policies. We demonstrate that a Moving-to-Opportunity type voucher, in which people residing in high poverty tracts are given a voucher to move to low-poverty tracts, does not affect child ability as households use the voucher to move to relatively inexpensive, low-impact neighborhoods. When vouchers are restricted such that they can only be applied in tracts with large effects on children, we demonstrate the total benefits of any voucher less than 700 per month exceed the costs and the voucher that maximizes total social surplus is 300 per month.
Keywords: I24; I31; I38; J13; R23; R38; 330; Neighborhood Choice; Neighborhood Effects; Moving to Opportunity; Vouchers